Case Report: Sustained Remission Due to PD-1-Inhibition in a Metastatic Melanoma Patient With Depleted B Cells - Wulfken, Lena Margarethe; Becker, Jürgen Christian; Hayajneh, Rami; Wagner, Annette Doris; Schaper-Gerhardt, Katrin; Flatt, Nina; Grimmelmann, Imke; Gutzmer, Ralf (Frontiers in Immunology, 2021)
Checkpoint-Inhibition (CPI) with PD-1- and PD-L1-inhibitors is a well-established therapy for advanced stage melanoma patients. CPI mainly acts via T-lymphocytes. However, recent literature suggests also a role for B cells modulating its efficacy and tolerability of CPI. We report a 48-year-old female patient with metastatic melanoma affecting brain, lung, skin and lymph nodes. A preexisting granulomatosis with polyangiitis was treated with rituximab over five years prior to the diagnosis of melanoma, resulting in a complete depletion of B cells both in peripheral blood as well as the tumor tissue. In the absence of a BRAF V600 mutation of the melanoma, treatment with the PD-1 inhibitor nivolumab was initiated. This therapy was well tolerated and resulted in a deep partial response, which is ongoing for 14+ months. Flow cytometric analysis of peripheral blood mononuclear cells revealed 15% IL-10 producing and 14% CD24 and CD38 double positive regulatory B cells. The exceptional clinical response to nivolumab monotherapy in our patient with depleted B cells sheds a new light on the relevance of B cells in the modulation of immune responses to melanoma. Obviously, B cells were not required for the efficacy of CPI in our patient. Moreover, the depletion of regulatory B cells may have improved efficacy of CPI.